Berita Penutupan Hotel Alexis di Media Online - Rety Palupi; Jaka Atmaja (Jurnal Komunikasi, 2018)
The phenomenon of Alexis hotel starts from its existence to its closing becomes the latest rumor. Two crucial points are, Alexis hotel is like ’paradise’ nightlife for men, and it is dismissed of the operational by the Governor of DKI Jakarta, which just inaugurated less than a month. While the mass media as the publisher of information to the public, fairly, roles neutrally. However, it is now not taboo anymore if the media presents things containing elements of its importance. This paper attempts to analyze specifically by using the V. Sigal parameter from the coverage of Alexis hotel. The author selects ten news which displayed by some online media. Afterwards, it is going to be analyzed by using five parameters, they are: Tone news, sources, sensitivity, balance, and placement. Eventually, the results is stated that althoug the Tone news is strongly negative, but the Alexis Hotel, a place for that has activities in the night, tend not to be to have the bad impact from ten discussed matters